2021
DOI: 10.1044/2020_aja-20-00140
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Audiology Graduate Programs: Training Students in Tinnitus Management

Abstract: Purpose Although tinnitus is highly prevalent among patients receiving audiology services, the extent to which most audiologists are trained in tinnitus management is not well documented. The extent and type of instruction in tinnitus clinical care provided by audiology graduate (AuD) programs is not clear, nor is it known whether training programs are consistent in their recommendations. It is certainly true that widely accepted standards do not exist to ensure that all tinnitus clinical services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…programs did not favorably rank their graduates' ability to counsel tinnitus patients (22% of graduates below average, 41% were ranked as average, and 38% were ranked above average). 15 The 22% of graduates who were found to be ranked as below average by Henry et al 15 are again very similar to the data collected from the responding audiologists in the present survey study, which indicates ∼20% of audiologists do not perform or refer for tinnitus counseling. Further standardization of tinnitus training, tinnitus assessment and management could improve audiologists' compliance with CPGs.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…programs did not favorably rank their graduates' ability to counsel tinnitus patients (22% of graduates below average, 41% were ranked as average, and 38% were ranked above average). 15 The 22% of graduates who were found to be ranked as below average by Henry et al 15 are again very similar to the data collected from the responding audiologists in the present survey study, which indicates ∼20% of audiologists do not perform or refer for tinnitus counseling. Further standardization of tinnitus training, tinnitus assessment and management could improve audiologists' compliance with CPGs.…”
Section: Discussionsupporting
confidence: 82%
“…graduates to address the tinnitus patient population found that only 68% of programs ranked their graduates as being well prepared to assess the functional and emotional impacts of bothersome tinnitus. 15 This percentage is an exact match to the sampled audiologists in the present study that indicated they deploy standardized questionnaires (68%), which largely aim at characterizing the functional and emotional impacts of tinnitus. 42 Furthermore, Henry et al 15 also reported that Au.D.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations